Fotocatálise solar heterogênea para degradação do contaminante azul de metileno usando nanoferritas - Bezerra, Fabiana Costa (2022)
The problems of environmental pollution have become increasingly serious with the advancement of human activities, causing degradation of natural resources, compromising the quality of life and, causing inevitable economic losses with environmental liabilities. More and more restrictive norms and legislation, as a result of a growing awareness of the harm caused by water pollution, have been adopted in order to mitigate the environmental impacts generated. From an environmental, social and economic point of view, there is great interest in the treatment of industrial effluents due to the potential of the polluting load and its difficult degradation by conventional treatment methods, which often occur inefficiently. With a view to offering an alternative solution that contributes to solving the major problems of effluent pollution, the aim of this work was to adopt a line of research aimed at a technology that degrades textile industrial effluents such as methylene blue dye (AM), under solar energy , based on the use of advanced nanoceramics (ferrites) as a photocatalyst. For this purpose, pure Ni0,5Zn0,5Fe2O4 ferrites doped with copper ions (Cu) ranging from 0 ≤ x ≤ 0.3 mol were used, known as prominent materials due to their inverted spinel structure that results in excellent properties , which were synthesized in a simple and fast way through the chemical method of the combustion reaction. The characterizations carried out by DRX, TG/DTG, BET/BJH, EDX and UV-Vis confirmed the good structural, thermal, textural and optical properties of the ferrites. The photocatalytic tests were divided into 03 distinct phases, with the preliminary phase starting from exploratory tests in jar test to analyze and compare the performance of pure Ni-Zn ferrite in relation to those doped with mol of Cu2+. Subsequently, taking into account those doped samples that after 2 hours of sun exposure showed better performance for the degradation of the AM dye, namely, the Ni-Zn ferrites doped with 0.2 and 0.3 of Cu2+, whose efficiencies were analyzed by an apparatus UV-Vis spectrophotometer were 79.3% and 97.4%, respectively. The second phase consisted of using a shaker table, along with a full 23 factorial design, adopting pure Ni-Zn ferrites and the one doped with 0.3 Cu2+ in order to find the optimal point to improve the solar heterogeneous photocatalysis process . The main interfering variables were the concentration of the photocatalyst (0.1 to 0.5 g/L), the concentration of hydrogen peroxide (H2O2) (90 to 110 mg/L) and the pH (3 to 5) of the samples. The ferrite doped with 0.3 mol of Cu2+ stood out with 93.03% efficiency in the planning, with the photocatalyst and H2O2 concentration being the most significant variables. Finally, in a third phase, this same ferrite was tested under optimal conditions, in a jar test, obtaining 97.8% efficiency. consecutive years it was still possible to obtain efficiency of up to 94.7%, which demonstrated significant stability for reinsertion in new photocatalytic processes, thus being a proven relevant alternative that contributes significantly to the advancement of research in the area of the use of contaminated effluents.